THE INFLUENCE OF THE APPLICATION OF THE CALCULATED SIMAK METHOD ON LEARNING OUTCOMES OF INDONESIAN LANGUAGE MATERIAL DESCRIPTION TEXT OF CLASS II, STUDENTS AT SDN NO. 125 INPRES BULUKUNYI TAKALAR - Djafar, Hamsiah; Rosdiana; Fitri Sikki (Educational Leadership: Jurnal Manajemen Pendidikan, 2023)
This study aims to find out the learning outcomes before and after the application of the guess-seeking method and whether there are differences in learning outcomes after the class II, implementation of the guess-seeking method at SDN No. 125 Inpres Bulukunyi Kab. Takalar. This type of research uses quantitative research with pre-experimental design one group pretest postets method. The population in this study were all class II, students at SDN No. 125 Inpres Bulukunyi, totaling 23 people. The data collection technique used is observation, testing and documentation. The instrument used is the learning achievement test. The analysis technique used is descriptive statistical analysis and inferential statistics. The results of the analysis show that the average value of learning outcomes before using the method is 40.78 in the medium category. While the average value of learning outcomes after being taught using the guesswork method of 74.87 is in the high category. The results of the hypothesis test show that there are differences in learning outcomes before and after being taught using the conjecture method, when viewed from the average post-test learning outcomes that are greater than the pre-test scores. So the application of the guess guess method has a positive influence on the results of learning Indonesian language description text material in class II, students at SDN No. 125 Inpres Bulukunyi, Takalar Regency.